Pengaruh Debt to Eguity Ratio (DER) Terhadap Harga Saham pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) periode 2019-2021 - Irwan Kejar Iman Teguh Hulu; Hendra Nazmi; Jhon Raphael Saragih (CV. Tungga Esti, 2023)
The purpose of this study is to determine and describe the effect of the debt to equity ratio (DER) on the stock prices of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The research method used is quantitative. The type of research used is quantitative descriptive research. This research is explanatory. Samples were taken using the Purposive Sampling method in the form of 56 manufacturing companies on the Indonesia Stock Exchange (IDX) during the 2019-2021 period. These results indicate that the DER variable has an effect on stock prices. This proves to be significant above 0.05. So when DER goes up, it affects stock prices. Simple regression analysis for this study gives a simple regression equation Y = 253.635 + 0.480. Then the determination test gives a correlation value (R) of 0.238 or 23.8% which indicates that the dependent variable and independent variable are positively correlated, meaning that if the DER increases, the stock price will also increase. The value of the coefficient of determination (adjusted R2) can have a DER effect on the dependent variable (stock price) which is indicated by R2 which is equal to 0.057.Keywords: Debt to Equity Ratio Stock Price